The role of Namibia Field Epidemiology and Laboratory Training Programme in strengthening the public health workforce in Namibia, 2012–2019. Issue 4 (13th April 2021) - Nyarko, Kofi Mensah; Miller, Leigh Ann; Baughman, Andrew L; Katjiuanjo, Puumue; Evering-Watley, Michele; Antara, Simon; Angula, Penehafo; Mitonga, Honore K; Prybylski, Dimitri; Dziuban, Eric J; Ndevaetela, Emmy-Else
Abstract : Namibia faces a critical shortage of skilled public health workers to perform emergency response operations, preparedness activities and real-time surveillance. The Namibia Field Epidemiology and Laboratory Training Programme (NamFELTP) increases the number of skilled public health professionals and strengthens the public health system in Namibia. We describe the NamFELTP during its first 7 years, assess its impact on the public health workforce and provide recommendations to further strengthen the workforce. We reviewed disease outbreak investigations and response reports, field projects and epidemiological investigations conducted during 2012–2019. The data were analysed using descriptive methods such as frequencies and rates. Maps representing the geographical distribution of NamFELTP workforce were produced using QGIS software V.3.2. There were no formally trained field epidemiologists working in Namibia before the NamFELTP. In its 7 years of operation, the programme graduated 189 field epidemiologists, of which 28 have completed the Advanced FELTP. The graduates increased epidemiological capacity for surveillance and response in Namibia at the national and provincial levels, and enhanced epidemiologist-led outbreak responses on 35 occasions, including responses to outbreaks of human and zoonotic diseases. Trainees analysed data from 51 surveillance systems and completed 31 epidemiological studies. The NamFELTP improved outcomes in the Namibia's public health systems; including functional and robust public health surveillance systems that timely and effectively respond to public health emergencies. However, the current epidemiological capacity is insufficient and there is a need to continue training and mentorship to fill key leadership and strategic roles in the public health system.